PSAK 112 Sebagai Penguatan Akuntabilitas Wakaf Saham ke Publik - Rini Muflihah (LPPM IAIT, 2023)
Nadzir is the party that receives waqf property from the Waqif to be managed and developed in accordance with its designation, but the accounting policies applied cause diversity, some nazir apply PSAK Number 109 Accounting for Zakat and Infaq / Alms as the basis for recording, on this basis nazir must be guided and educated for the application of PSAK Number 112 concerning waqf, especially for cash waqf nazir including waqf shares, which are expected to provide accountable and transparent financial reports. The purpose of this study is to provide an illustration of waqf shares based on PSAK Number 112 concerning Waqf Accounting. This research uses literature study. The results of this study are in the form of illustrations of waqf stock transactions with journal entries based on PSAK No. 112 on Waqf Accounting in accordance with the recognition, measurement, disclosure, and presentation of financial statements.